IMPROVING STUDENTS' CLASSROOM BEHAVIOUR BY MAXIMIZING TEACHER-STUDENT INTERACTION DURING CLASS - Purnama Nancy F. Lumban Batu (Soegijapranata Catholic University, 2010)
Behaviour is one thing that is really important in one's life achievement. Behaviours will develop into character that defines one's future. Further, a research of Swick shows that a student's behaviour in the classroom significantly affects his/her behaviour outside the classroom, as in the real world. This article is focusing on a way to improve the students' behaviour in the classroom. Teachers, as students' motivator and role model, can encourage them to improve their behaviour through the limited learningprocess at school. It not through the presented material, yet it is through the way the material is presented in the class, the interaction led by the teacher. This article is trying to apply the communication science into classical teaching-learning process related to Skinner behaviourism theory. The better the stimulus, the better the response will be. Interaction is. seen as the stimulus and the students' behaviour is seen as the response to it. The better the interaction, the better the behaviour will be.